Plasma Levels of Activated Factor VII Decrease during the Menstrual Cycle - Kapiotis, Stylianos; Jilma, Bernd; Pernerstorfer, Thomas; Stohlawetz, Petra; Eichler, Hans-Georg; Speiser, Wolfgang (Thrombosis and Haemostasis, 1998)
Men have an increased cardiovascular risk as compared to women, which is largely ascribed to the cardioprotective effects of female sex steroids. We hypothesised that this may be reflected by differences in the activation status of the coagulation system. Hence the aim of this study was to compare plasma levels of activated factor VII (FVIIa) in men and women, and to study the influence of the menstrual cycle on FVIIa levels.In a prospective study we investigated 20 healthy young women and 20 men. Men had significantly higher levels of activated factor VII (60 mU/ml, CI: 52 to 67) than women during all phases of the menstrual cycle. In women FVIIa was higher during the follicular phase (41 mU/ml, CI: 33 to 50) than during midcycle (34 mU/ml, CI: 24 to 45; p = 0.022 vs. follicular phase) and during the luteal phase (33 mU/ml, CI: 24 to 42; p = 0.006 vs. follicular phase). Prothrombin fragment (F1 + 2) levels decreased from 0.86 nmol/l (CI: 0.51-1.21) by -23% (-39% to -8%; p = 0.011) during midcycle and by -25% (CI: -51% to 1%; p = 0.023) during the luteal phase.These data support the contention that plasma levels of FVIIa, a key enzyme of the coagulation cascade, may be down-regulated by endogenously produced female sex hormones during the menstrual cycle. This may at least partially explain the marked gender differences found in FVIIa.